Genericity and Metaphoricity Both Involve Sense Modulation - VOGEL, CARL (Springer, 2011)
An approach to sense extension tailored for polysemy associated with non-literal language is expanded to include belief revision generally. The relationship between metaphor and genericity as rhetorical devices is discussed, and both are accounted for as related species within the same framework of dynamic semantics. The theoretical apparatus is related to a dominant theory of metaphor interpretation and processing which holds metaphorical utterances to be class inclusion statements involving dual reference for the the metaphorical vehicle.
Affective Computing and Sentiment Analysis: Emotion, Metaphor and Terminology
PUBLISHED
Text, Speech and Language Technology. Volume 45
Dordrecht
Keywords: Computer and information sciences; Metaphors; Sense-extension; Belief-revision; Creative Technologies; Digital Humanities; Intelligent Content & Communications; Computational linguistics